Análisis De La Práctica Creativa Musical En Educación Primaria Como Base Para El Diseño Y Desarrollo De Una Herramienta Metodológica De Evaluación Didáctica - Aranda, Luis del Barrio (European Scientific Journal, ESJ, 2017)
This study focuses on the analysis of musical creativity as a capacity of self didactics favoring the development of the autonomy of the student in Primary education. Our goal is to design and develop a tool of evaluation of the musical knowledge of the student in creative practice that serves as the basis for the orientation of the educational process. To do this, we carry out an ethnographic research with a class group of 26 pupils of fourth of Primary school who performed sixty creative tasks during two school years. The results obtained from the analysis of the works of children have shown that systematic creative activity stimulates musical thinking, hearing, musicalverbal expression and critical analysis and provides the student a greater confidence and security in the undertaking of new challenges. At the end of the study, analysis of productions has improved the design of a methodological tool capable of analyzing the musical knowledge of the student in a creative educational process.